Novel Psychoactive Substances in Custodial Settings: A Mixed Method Investigation on the Experiences of People in Prison and Professionals Working With Them - Corazza, Ornella; Coloccini, Sara; Marrinan, Shanna; Vigar, Mike; Watkins, Caryl; Zene, Cosimo; Negri, Attilio; Aresti, Andreas; Darke, Sacha; Rinaldi, Raffaella; Metastasio, Antonio; Bersani, Giuseppe (Frontiers in Psychiatry, 2020)
Novel Psychoactive Substances (NPS), especially Synthetic Cannabinoid Receptor Agonists (SCRAs), pose a substantial challenge to health and the security of the the prison environment. This study analyses the phenomenon from the perspective of people in prison and that of professionals working with them. Methods: A phenomenological qualitative approach was used to analyse self-reported experiences with ‘Spice’ (NPS) among users in prison. A semi-structured questionnaire was also disseminated among professionals working in these settings to better understand (a) the impact of NPS on their work; (b) perceived issues on safety in their working environment; (c) approaches used to tackle the phenomenon and best practices. Results: Psychotic events resulting from the collected Spice accounts (5) were marked by hallucinations, depression, self-harm, and suicidal ideations. Other emerging elements included fear, paranoia, inability to be with others, mistrust, breakdown and other risky behaviours. Overall, 186 responses from prison staff were collected across the country. 67% claimed NPS to have had a deep impact on their work as they commonly witnessed espisodes involving outbursts of anger, slurred speech, hallucinations, psychosis, and significant mental deterioration among those in prison. 91% had witnessed aggression at least once, with 53% experiencing direct harm. Suggested interventions included enhanced training and education (84%), improved detection (92%) and treatment and support services (93%). Conclusions: Findings highlight the urgent need for joint multi-disciplinary efforts to tackle the exponential escalation of NPS in prisons as well as to facilitate the recovery and societal reintegration of those affected. Phenomenology can be recommended as a valuable methods to study drug induced experiences.